Major Antecedents of Electronic Customer Relationship Management (E-CRM) Studies in the Indian Banking Sector : A Systematic Review - Shetty, Prashanth; Y., Poornima (Indian Journal of Marketing, 2023)
Purpose: Through a comprehensive literature review using PRISMA criteria, the current study identified the primary antecedents of electronic customer relationship management (e-CRM) employed by prior studies across the Indian banking sector. Methodology: The authors systematically reviewed peer-reviewed articles in the context of Indian banking. The study followed the PRISMA standards. Related keywords are improved and tested against various databases. Thirty-three research articles were considered for review after meeting the eligibility criteria. Findings: The study highlighted customer perception and satisfaction as the significant antecedents of e-CRM research for the Indian banking sector. Additionally, the study showed more studies on the customer’s perspective than the banker’s perspective. Only a few studies used qualitative approaches in the context of e-CRM research. Practical Implications: This study examined the evolution of e-CRM research in the Indian banking setting in terms of study categories, important antecedents, study kinds, data collection methods, sample sizes, and under and over-researched areas. Originality: The study appeared to be the first of its kind for the Indian banking sector, adding new knowledge to the body of literature on e-CRM by taking into consideration the synthesis and summarization of the significant antecedents used across all the empirical studies of e-CRM in the Indian banking sector through systematic literature review.